Declining winter snowpack offsets carbon storage enhancement from growing season warming in northern temperate forest ecosystems - Emerson Conrad-Rooney; Andrew B. Reinmann; Pamela H. Templer (Proceedings of the National Academy of Sciences, 2025)
Northeastern US temperate forests are currently net carbon (C) sinks and play an important role offsetting anthropogenic C emissions, but projected climatic changes, including increased temperatures and decreased winter snowpack, may influence this C sink over the next century. Past studies show that growing season warming increases forest C storage through greater soil nutrient availability that contributes to greater rates of net photosynthesis, while reduced winter snowpack induces soil freeze/thaw cycles that reduce tree root vitality, nutrient uptake, and forest C storage. The year-round effects of climate change on this C sink are not well understood. We report here decade-long results from the Climate Change Across Seasons Experiment (CCASE) at the Hubbard Brook Experimental Forest, which determines the combined effects of growing season warming and a smaller winter snowpack on C storage in northern temperate forests. We found after a decade of treatments that growing season warming increases cumulative tree stem biomass C by 63%. However, winter soil freeze/thaw cycles offset half of this growing season warming effect. The amount of C stored in stem biomass of trees experiencing both growing season warming plus smaller winter snowpack is only 31% higher than the reference plots, but this difference is not significant. Our results suggest that current Earth system models are likely to overestimate the C sink capacity of northern temperate forests because they do not incorporate the negative impacts of a shrinking snowpack and increased frequency of soil freeze/thaw cycles on C uptake and storage by trees.